ANALISIS PENGARUH VARIABEL EKONOMI MAKRO TERHADAP RETURN SAHAM PADA INDUSTRI FARMASI - Heliyani, Heliyani (jurnal ekonomi, 2007)
The investor will try to see micro and macro economic condition in considering such stock due to it can influence the return of the stock. Return is the motivator in the infestations process. Therefore, the investors in comparing samoe investation's alternative ganerally use return measurement. The aim of tihs rasearch is to analyze factor variable macro economic of the stock toward stock return. Economic variable use rate of inflation and interest rate SBI. Nine pharmacy enterprises registered in the unit of research analysis at Jakarta Stock Exchange from 2001 to 2005. Eviews program used to prove the hypothesis by hte regression. The result of the research is there are rate SBI of the stock that have the significant influence toward the stock return pharmacy enterprices.